PERAN PERLINDUNGAN ANAK TERPADU BERBASIS MASYARAKAT (PATBM) DALAM UPAYA MENCEGAH KEKERASAN TERHADAP ANAK DI PROVINSI BANTEN - Denna Ritonga; Nina Chairina (Program Studi Hukum Tata Negara (Siyasah) IAIN Palopo, 2026)
Children are a trust from Allah SWT. Inherent in every child is a high sense of dignity and worth as a fully-fledged human being. From the moment of conception, children possess rights that must be protected, fulfilled, and respected. These rights are based on the principle of the best interests of the child, the right to life and survival, non-discrimination, and respect for the child’s views—meaning these rights are not merely for the child’s survival but also to realize the best interests of the child, applicable to all children without discrimination, and implemented by respecting the child’s views. Efforts to protect children are carried out by various stakeholders, one of which is the Community-Based Integrated Child Protection (PATBM) in Banten Province. The research questions in this study are: (1) What is the role of PATBM in Banten Province in efforts to prevent violence against children, and (2) What factors constitute challenges and obstacles for PATBM in Banten Province. The research questions in this study are: (1) What is the role of the Banten Province Child Protection Agency (PATBM) in efforts to prevent violence against children, and (2) What factors constitute obstacles and barriers for the PATBM in Banten Province? This study employs an empirical legal research method to examine the role of the PATBM regarding children. The findings indicate that the role of the PATBM in Banten Province is based on the Child Protection Law as well as local regulations, including both provincial regulations of Banten and district/municipal regulations. This role is carried out through outreach and education on children’s rights, prevention, intervention, and recovery. PATBM provides medical, legal, and psychological protection. However, in practice, there are challenges and obstacles, including the public’s reluctance to report incidents of violence or serve as witnesses, the perception that what occurs within a household is the family’s private domain and that publicizing it is a source of shame, and the public’s lack of knowledge regarding legal protections against violence against children.